Social change in Kerala :insights from micro-level studies - Nair,K.N.(Editor) Vineetha Menon(Editor) (Studies in local-level development, 2007)
Contributed articles developed as part of Project on Village Restudies in South India initiated by the Kerala Research Programme on Local Level Development.